2010
DOI: 10.1002/ange.201005061
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticles End‐Capped with Collagen: Redox‐Responsive Nanoreservoirs for Targeted Drug Delivery

Abstract: Das Anbringen von Collagen (Col) an Siliciumoxid‐Nanopartikel (MSNs) über eine Disulfidbrücke und die anschließende Einführung von Lactobionsäure (LA) als zielführende Einheit ergaben ein redoxresponsives System für den zellspezifischen intrazellulären Wirkstoff‐Transport und die effiziente Endozytose (siehe Bild). Die kontrollierte Freisetzung des Modellwirkstoffs Fluoresceinisothiocyanat (FITC) gelang durch Spaltung der Disulfidbrücken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 24 publications
(21 reference statements)
3
132
0
1
Order By: Relevance
“…Among these new systems, silica mesoporous nanoparticles, especially MCM-41 (Mobil Catalytic Material Number 41) and SBA-15 (Santa Barbara Amorphous- 15), have been proposed as new drug delivery systems in recent years due to their ability, through strong chemical interactions, to incorporate molecules of therapeutic interest [8][9][10][11]. Furthermore, in some studies, these nanoparticles have demonstrated that the release process can be controlled by redox reactions [12,13], pH variations [14,15], competitive binding [16], or functionalization with different compounds, such as alkyl-silanes and methacrylic acid [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Among these new systems, silica mesoporous nanoparticles, especially MCM-41 (Mobil Catalytic Material Number 41) and SBA-15 (Santa Barbara Amorphous- 15), have been proposed as new drug delivery systems in recent years due to their ability, through strong chemical interactions, to incorporate molecules of therapeutic interest [8][9][10][11]. Furthermore, in some studies, these nanoparticles have demonstrated that the release process can be controlled by redox reactions [12,13], pH variations [14,15], competitive binding [16], or functionalization with different compounds, such as alkyl-silanes and methacrylic acid [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the contemporary silica-based, biothiol-mediated release systems are established with similar setups. Cap or gatekeeper molecules such as collagen [34], DNA [35,36], polymer molecules [37,38], gold nanoparticles [39], and cyclodextrin [40,41] have been employed to functionalize the surface of mesoporous silica nanoparticles using disulfide linkers for enabling the redox-responsive off/on drug release. However, few studies [42,43] have focused on exploiting the inherent properties of silica materials to achieve self-modulations in the intracellular milieu and to improve cytosolic bioavailability.…”
Section: Resultsmentioning
confidence: 99%
“…Zhong Luo and Kaushik Patel et al have used collagen and cyclodextrine as gatekeepers to realize controlled drug release, but the grafting density of gatekeepers has not been investigated in their studies (Luo et al, 2011;Patel et al, 2008;Zhang et al, 2014). In our research, for the first time, we investigated the effects of grafting density of gatekeepers on the drug release and the biocompatibility of silica carriers.…”
Section: Introductionmentioning
confidence: 88%